Inhibition of Angiotensin II Gq Signaling Augments β-Adrenergic Receptor Mediated Effects in a Renal Artery Stenosis Model of High Blood Pressure - Harris, David M. (2008)
Chronic ventricular pressure overload states, such as hypertension, and elevated levels of neurohormones (norepinephrine, angiotensin II, endothelin-1) initiate cardiac hypertrophy and dysfunction and share the property of being able to bind to Gq-coupled 7-transmembrane receptors. The goal of the current study was to determine the role of endogenous cardiac myocyte Gq signaling and its role in cardiac hypertrophy and dysfunction during high blood pressure (BP). We induced renal artery stenosis for 8 weeks in control mice and mice expressing a peptide inhibitor of Gq signaling (GqI) using a 2 kidney, 1 clip renal artery stenosis model. 8 weeks following chronic high BP, control mice had cardiac hypertrophy and depressed function. Inhibition of cardiomyocyte Gq signaling did not reverse cardiac hypertrophy but attenuated increases in a profile of cardiac profibrotic genes and genes associated with remodeling. Inhibition of Gq signaling also attenuated the loss of cardiac function. We determined that Gq signaling downstream of angiotensin II receptor stimulation negatively impacted β-adrenergic receptor (AR) responses and inhibition of Gq signaling was sufficient to restore βAR-mediated responses. Therefore, in this study we found that Gq signaling negatively impacts cardiac function during high BP. Specifically, we found that inhibition of AT1-Gq signaling augmented βAR mediated effects in a renal artery stenosis model of hypertension. These observations may underlie additional, beneficial effects of angiotensinogen converting enzyme (ACE) inhibitors and angiotensin receptor antagonists observed during times of hemodynamic stress.